BACTERIOLOGICAL DETECTION OF VIRIDANS GROUP STREPTOCOCCI ASSOCIATED WITH DENTAL CARIES IN THIQAR PROVINCE - Basim Jasim Mohammed; Secil Akilli Simsek; Amany Shakeir Jaber (Scholar Express Journals, 2023)
This is a study conducted in Al-Nasiriya City-Dhi Qar province/ Iraq for the period from August 2020 to Jun 2021. A total of 250 dental caries swabs were collected from patients with dental caries (DC). . The age range was 7-59 years, 159 (63.6%) were males and 91 (36.4%) were females. The results found that the SVG isolation rate from dental caries was 128 (51.2%). The age group 40- 49 years had significantly higher isolation rate (P= 0.005). Females had insignificantly higher rate of isolation (P= 0.915) compared to males. Urbanees had insignificantly higher isolation rate compared to rularees (P= 0.112). Smoking patients had insignificantly higher isolation rate (P=0.781). Generally, patients with comorbidities and particularly those with DM had significantly higher isolation rate of SVG (P= 0.0001). Neither site, frequency nor duration of DC had significant effect on the isolation rate of SVG. On the other hand, the presence of periodontitis had significantly increase the isolation rate (P= 0.0001). While the presence of pain, swelling and the dental care had no effect on the isolation rate. Consumption of snacks was found to be as insignificantly increase the isolation rate. The 6.0 pH of saliva was found to be associated with insignificantly increase in SVG isolation rate (p = 0.767). The results also found that 86.0% of the isolates produce proteases and 87.0% were alpha hemolytic. Additionally, 38.0% and 56.2% of the isolates were strong and moderate biofilm former
Keywords: Dental Caries; Streptococcus Viridans; Periodontal Disease; Tooth Decay